Toxic Gases on β12 Borophene: the Selective Adsorption - Thi Luong, Ta; Trong Lam, Pham; An, Dinh Van (VNU Journal of Science: Mathematics - Physics, 2020)
Borophene, a new member of the 2D material family, was proven theoretically and empirically in many recent studies that it has a unique structure and promising properties applied in batteries and electronic devices. In this work, the adsorbability of β 12 – borophene towards some main poisonous gases was investigated. Herein, first-principle calculations were employed to obtain the adsorption configurations, adsorption energy of CO, NO, CO 2 , NH 3 , and NO 2 on b 12 – borophene by using three van der Waals correlation functionals: revPBE-vdW, optPBE-vdW, and vdW-DF2. Also, the most stable configurations and diffusion possibilities of the gas molecules on the surface of b 12 – borophene were determined visually by using Computational DFT-based Nanoscope. The nature of bonding and interaction between gas molecules and b 12 – borophene were disclosed by using the density of states analysis and Bader charge analysis. Remarkably, borophene exhibits as a highly selective adsorbent when having great interactions with NO x gases outweigh the others.